The Development of Interactive Powerpoint Learning Media to Increase Students’ Critical Thinking Ability - Ramdan, Muhamad; Anita, Ika Wahyu ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
Mathematics learning can develop students' creativity to solve problems in various life situations. Learning mathematics helps train students to think critically and creatively to solve problems. Considering the reality on the ground and the importance of critical thinking skills. from an early age. One effort to develop critical thinking abilities is to use media directed at these abilities. The method used in this research is research and development, with a modified 4-D development model in three stages, namely determination, design and development. This research aims to determine the development of interactive teaching materials assisted by power points, on Statistics material. The subjects of this research were 3 mathematics teachers at SMP Mutiara 4 Bandung. The instrument for developing teaching materials uses interview instruments. The teaching materials validated by three validators have a total score on the interactive power point of 275 with a maximum ideal score of 300 and have a percentage of 92.31% in the valid category based on the teaching material criteria. The validator's assessment of the interaction strength score shows that the percentage score for each aspect and the total percentage score are both in the valid category. Based on the research and development process and results, the following conclusions were obtained. Developing learning media using interactive Powerpoint, critical thinking skills are within valid criteria. The results obtained can be tested on junior high school or MTs students in accordance with the considerations and assessments of validator experts.